Pd(II)‐Catalyzed Chelation‐Induced C(sp2)‐H Acylation of (Hetero)Arenes Using Toluenes as Aroyl Surrogate. Issue 44 (23rd November 2021) - Joshi, Asha; Iqbal, Zafar; Jat, Jawahar L.; De, Saroj R.
Abstract: In the last few years, transition‐metal‐catalyzed chelation‐controlled ortho ‐acylation utilizing methyl arene as the acyl partner has emerged as a powerful technique to achieve diverse complexity with diaryl ketone skeleton contrast to the traditional cross‐coupling/Friedel‐Craft reaction. Diaryl ketones are a significant building block that exists in pharmaceuticals, agrochemicals, natural products, functional materials, and many other useful compounds. In this context, the up‐to‐date developments in Pd(II)‐catalyzed ortho ‐acylations of arenes and heteroarenes with toluenes as acyl surrogate are studied with advantages, limitations, mechanistic pathways, and prospective. Abstract : The up‐to‐date advancements on Pd(II)‐catalyzed C(sp 2 )‐H acylation of (Hetero)arenes using toluenes as aroyl surrogate are being summarized herein to provide an overview achieving important diaryl ketone skeleton present in natural products, functional materials, biological, and agrochemicals compounds.